MXene-containing composite electrodes for hydrogen evolution: Material design aspects and approaches for electrode fabrication. (23rd March 2021) - Sergiienko, Sergii A.; Lopes, Daniela V.; Constantinescu, Gabriel; Ferro, Marta C.; Shchaerban, Nataliya D.; Tursunov, Obid B.; Shkepu, Viacheslav I.; Pazniak, Hanna; Tabachkova, Nataliya Yu.; Castellón, Enrique Rodríguez; Frade, Jorge R.; Kovalevsky, Andrei V.
Abstract: This work explores the possibilities for the processing of Ni- and Ti3 C2 Tx (T = OH, O) MXene-containing composite electrodes, by co-pressing and plastic deformation or by etching of the electrodes prepared directly by self-propagation high-temperature synthesis (SHS). Various material design approaches were also explored. In order to tune the Ti3 C2 interlayer distance in Ti3 C2 Al MAX phase, an introduction of additional Al to form Ti3 C2 Alz materials with z > 1 was attempted. Self-propagation high-temperature synthesis of powder mixtures with extra Ni and Al content (e.g. Ni:Ti:Al:C = 1:2:3:1) resulted in SHS products containing Ti3 C2 Alz z > 1 material and Ni–Al alloys. Further etching of these products in 10M NaOH allowed the direct formation of electrodes with active surface containing Ti3 C2 Tx (T = OH, O) MXene- and Raney nickel-containing composites. The electrochemical studies were focused on hydrogen evolution and showed the potential for boosting the electrochemical reaction in Ni and MXene-containing composite electrodes, especially at high current densities. The guidelines for the processing of such electrodes under fluorine-free conditions are proposed and discussed. Highlights: Ti3 C2 Alz (z > 1) MAX phases containing Al excess were synthesized. The composites based on Ni–Al alloy and Ti3 C2 Alz phase (z > 1) were obtained. Processing of MXene-containing electrodes under F-free conditions is demonstrated. Etching in alkaline medium forms active MXene- and Ni-containing surface layer. MXene- and Ni-containing electrodes show enhanced activity towards the HER.